Fourfold magnetic anisotropy induced in CoFeB/IrMn bilayers by interfacial exchange coupling. (1st February 2023) - Feng, Xinwei; Meng, Jing; Zhu, Xiaoyan; Xue, Kelei; Xie, Yali; Jiang, Dongmei; Xu, Yang; Shang, Tian; Hu, Yong; Zhan, Qingfeng
Abstract: Exchange bias (EB) occurring in ferromagnetic (FM)/antiferromagnetic (AFM) bilayers conventionally can lead to a unidirectional magnetic anisotropy ( K eb ) as well as an accompanied uniaxial magnetic anisotropy ( K u ). We observed an additional fourfold magnetic anisotropy ( K 4 ) induced by interfacial exchange coupling in amorphous CoFeB/epitaxial IrMn bilayers with an EB. Because of the combined effect of the three kinds of magnetic anisotropies, one- and two-step magnetic switching processes were observed at different magnetic field orientations, which usually appear in single-crystal FM layer with an intrinsic magnetocrystalline anisotropy but not in amorphous FM layer. The angular dependent magnetic switching fields can be nicely fitted by a phenomenological model based on domain wall nucleation and propagation with the in-plane K 4 along <100>. The ferromagnetic resonance measurements indicate that the specific strength of K 4 for EB along [100] is larger than that for EB along [110]. The induced K 4 can be understood by considering two types of AFM domains caused by both monatomic steps and defects and their induced net uncompensated spins along the in-plane <100> axes. The different dependence of K 4 on the EB direction are because of the different effects of growth magnetic field on the presence of AFM domains.